Agrobacterium rhizogenes-Mediated Hairy Root Transformation in Rosa - Jun Lu; Yuwen Huang; Yuhan Guo; Chunguo Fan; Guozhen Yuan; Rui Zhou; Jingjing Sun; Mengjuan Bai; Kun Wang; Jinyi Liu; Changquan Wang (Horticulturae)
Roses (Rosa spp.) are widely used as ornamental plants and cut flowers and in perfumes and cosmetics; therefore, they have extremely high ornamental and economic value. Improving ornamental qualities (color, aroma, flower shape, plant architecture, petal senescence), agronomic traits (disease resistance, stress tolerance), and other traits would add value to cultivated roses. However, the lack of an efficient genetic transformation system limits functional genetic studies of roses. Therefore, we aimed to develop a simple, high-throughput Agrobacterium rhizogenes-mediated hairy root transformation system to analyze gene function in rose. We explored the factors affecting the induction and transformation of hairy root cultures in rose by screening different types of explants, Rosa genotypes, Agrobacterium strains, media, and infection and co-cultivation times for genetic transformation under aseptic conditions. We established an A. rhizogenes-mediated hairy root transformation system in rose using A. rhizogenes strains MSU440 and Ar Qual, successfully obtained transgenic hairy roots, and conducted preliminary experiments to examine their regeneration by employing the ultraviolet light (UV)-visible reporter eYGFPuv as a marker. Finally, we established a simple hairy root transformation process under non-aseptic conditions. The rapid and efficient transformation system developed here will enable efforts to investigate gene function in roses and engineer improved rose varieties. Refining the transformation protocol to work under aseptic and non-aseptic conditions will allow researchers to use this system efficiently and broadly.